The impact of service learning on the training of pre-service teachers: Analysis from a physical education subject - Gil-Gómez, Jesús; Chiva-Bartoll, Óscar; Martí-Puig, Manuel (European physical education review, 2015)
This paper discusses the effects of the use of service learning in pre-service teachers (PSTs). This methodology has been applied for two academic years at a Spanish university, providing a direct service for children with special educational needs (SEN) through motor and expressive games. We used Butin's model for the analysis of data collected through written reflections. The results show significant academic and personal learning, especially in areas useful for future teachers. The paper also proposes an extension (subcategories) of the original explanatory model. Verf.-Referat.